Experimental Investigation and Finite Element Analysis of Composite Conical Structures Subjected to Slip Loading - Aljibori, Hakim S. Sultan (2006)
One of the main objectives of aircraft and automotive manufacturers is related to improvement of the crash behaviour of lightweight structures. The absorbed energy is an important parameter for the development of the vehicle passive security concept. An energy absorption device is a system that converts totally or partially kinetic energy into another form of energy during collision, which is required of an ideal energy absorbing material, is to have the capability of dissipating as much energy as possible per unit weight/ volume. The increasing demand of composite structures in wide range of engineering applications, structures made from composite materials offers important characteristics such as weight reduction, design flexibility and safety improvement. These composite structures provide higher or equivalent crash resistance as compared to their metallic counterparts and therefore find for its using in crashworthiness applications. Polymer composite materials have been introduced in the automotive industry primarily to reduce the overall weight of the vehicle, which results in energy economy and for better fuel cost. However, the current trend in producing lighter structures puts greater demands on the design of more efficient energy dissipating systems.